The effect of altitude training on some physiological indicators in long-distance runners Field study of the runners of the youth sports team Jamoura - U17 - chetioui malek; قلاتي يزيد (sports creativity, 2025)
The main objective of this study was to investigate the effect of altitude training on the physiology of body organs in the sense of physiological adaptation and the intended benefit of such training on physical performance after returning to sea level for competitions. Given the importance of the functions of these organs (blood circulatory system, respiratory system and muscular system) in the provision of oxygen and transport and then extracted, we measured the efficiency of these functional devices through the use of several methods, including field tests, which are tests "Brixi" and "Barash" to measure the ability This study led to highlighting and interpreting the physiological aspects of the athlete in a more comprehensive sense and we discussed the effect of physiological adaptations resulting from the athletic training process in the highlands. The performance of these devices at sea level, we were selected for the sample of six players representing the half-long runners, and the benefits of this study was to allow us to stand clearly on the importance of preparedness and the desired objectives of such trainings. The physiological responses of respiratory, circulatory, and adaptive systems to physical changes in heights are counted